Impact of smoking on microRNAs in significant coronary artery disease - Hajsadeghi Shokoufeh; Iranpour Aida; Mirshafiee Shayan; Nekouian Reza; Mollababaei Maryam; Motevalli Hamed; Yasin Ahmadi Seyyed Amir; Dakkali Mohammad Sedigh (Romanian Journal of Internal Medicine)
Given the importance of coronary artery disease (CAD) and the range of cardiovascular disease phenotypes in smokers, as well as the potential genetic and epigenetic factors, we were motivated to explore the impact of smoking on some selected microRNAs associated with significant CAD.